2015
DOI: 10.17722/ijme.v5i1.797
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Infrastructure on Foreign Direct Investment in Malaysia

Abstract: FDI is an important contributor to the development and the transformation of the Malaysian economy, particularly in establishing new industries, enhancing production capacity, employment, trade and technological capability. This study aims to investigate the role of infrastructure on FDI in Malaysia from 1980 to 2013. Time series Malaysian data is used to capture the impact of infrastructure on FDI through ARDL method. The results revealed that besides GDP and exchange rate, infrastructure also had positive im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
1
6
1
Order By: Relevance
“…As seen in Model 5, considering the coefficients of the variables, lnRTRANSPORT has the most significant positive effect (1,8030) on lnRFDI. It has been determined that, except for the trade openness, the findings obtained in the study were found to be in parallel with the literature (Tufaner and Şirin, 2021;Khadaroo and Seetanah, 2010;Wheeler and Mody, 1992;Loree and Guisinger, 1995;Mike and Oransay, 2015;Morisset, 2001;Azolibe et al, 2020;Asiedu, 2002;Pradhan et al, 2013;Bakar et al, 2012;Rehman et al, 2011;Ahmad et al, 2015). While the trade openness ratio is expected to affect the inward FDI positively, the findings do not match the literature.…”
Section: Methodology Descriptives Empirical Results and Discussioncontrasting
confidence: 49%
“…As seen in Model 5, considering the coefficients of the variables, lnRTRANSPORT has the most significant positive effect (1,8030) on lnRFDI. It has been determined that, except for the trade openness, the findings obtained in the study were found to be in parallel with the literature (Tufaner and Şirin, 2021;Khadaroo and Seetanah, 2010;Wheeler and Mody, 1992;Loree and Guisinger, 1995;Mike and Oransay, 2015;Morisset, 2001;Azolibe et al, 2020;Asiedu, 2002;Pradhan et al, 2013;Bakar et al, 2012;Rehman et al, 2011;Ahmad et al, 2015). While the trade openness ratio is expected to affect the inward FDI positively, the findings do not match the literature.…”
Section: Methodology Descriptives Empirical Results and Discussioncontrasting
confidence: 49%
“…Infrastructure One of the factors that can influence FDI is infrastructure. This has been evidenced by many previous studies such as (Nguea, 2020;Sabir et al, 2019;Amune and Ogunjimi, 2019;Raghdsifa et al, 2018;Wekesa et al, 2016;Ngangue, 2016;Nourzad et al, 2014;Ahmad et al, 2015 Mohammadvandnahidi et al, 2012;Rehman, 2011;Seetanah and Khadaroo, 2009). They produced mixed findings on the effect of infrastructure on FDI, albeit with different methods.…”
Section: Literature Reviewsupporting
confidence: 57%
“…Mohammadvandnahidi et al (2012); Ahmad et al (2015); Amune and Ogunjimi (2019); Nguea (2020) used the ARDL approach to study the long-run and short-run relationships between FDI and infrastructure. Mohammadvandnahidi et al (2012) covered data between 1975 and 2007 in Iran.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…He claims the theory is unable to justify the surges in succeeding FDIs. Bakar et al (2012), conducted a study on the impact of infrastructure on foreign direct investment, the case of Malaysia and established a positive and significant influence of infrastructure Ahmed et al (2015), analyzed the impact of infrastructure on foreign direct investment in Malaysia and found out that infrastructure is a significant determinant of foreign direct inflows into Malaysia. Other factors like GDP and Exchange rate were also found to be significant.…”
Section: The Eclectic Theorymentioning
confidence: 99%